Models of Commercialization of Innovations in an Open Innovation Process - Zachłowski, Patryk (Olsztyn Economic Journal, 2022)
At present, innovations constitute a key determinant of a competitive position among market entities. Recent years have seen a change in the approach towards innovations and a gradual shift from a closed to an open model of innovation. The changing paradigm of innovation is accompanied by the question how to commercialize about outcomes of open innovation processes. The aim of the present article is to review models of the commercialization of innovations which are applied in innovation processes based on principles typical of the open innovation model.